The long term results of the Ross procedure: The importance of candidate selection. (1st December 2020) - Pergola, Valeria; Di Salvo, Giovanni; Fadel, Bahaa; Galzerano, Domenico; Al-Shaid, Maye; Al-Admawi, Mohammad; Al Amri, Mohammed; Al-Ahmadi, Mamdouh; Al-Halees, Zohair
Abstract: The Ross procedure has been considered in children as an optimal surgical procedure due to potential growth of the aortic annulus, lack of anticoagulation requirement, very low morbidity rate and excellent survival. Five-hundred-thirty-six (366 male, mean age 29.4 ± 11.1 years) underwent Ross procedure between 1990 and 2016 and had complete clinical and echocardiographic follow-up. Mean follow-up was 16.3 ± 4.9 years. Patients were divided in 2 groups according to age at surgery. Group 1 consisted of 320 (60%) patients less than 18 years old (223 male, mean age at surgery of 9.5 ± 5.6 years). Group 2 consisted of 216 (40%) patients older than 18 years of age (143 male, mean age at surgery of 26.3 ± 8.2 years). One-hundred-thirty (24%) patients had a redo procedure or surgery. Freedom from all re-operation and or percutaneous reintervention on either the aortic and pulmonary valves was 99% after 1 year, 94% after 5 years, 89% after 10 years, 83% after 15 years and 78% after 20 years. Freedom from redo surgery for AV 99% after 1 year, 94% after 5 years, 90% after 10 years, 81% after 15 years and 80% after 20 years. Freedom from redo surgery for PV was 100% after 1 year, 95% after 5 years, 89% after 10 years, 78% after 15 years and 76% after 20 years. The ideal candidate for Ross operation is a patient with congenital aetiology and an aortic root diameter ≤ 15 mm/m 2 . A pulmonary fresh preserved homograft seems to perform better on the long term. Highlights: The use of the Ross procedure represents <1% of all aortic valve replacements. Freedom from all re-operation was 89% after 10 years and 83% after 15 years. Freedom from redo surgery for AV was 90% after 10 years and 81% after 15 years. Rheumatic valves and aortic root diameter > 15 mm/m2 have worse outcome. A pulmonary fresh preserved homograft seems to perform better on the long term.